Shared Positivity in Daily Life of Younger and Older Couples: Links Between We-ness and Positive Emotions. (17th December 2021) - Meier, Tabea; Huber, Zilla; Dworakowski, Olenka; Haase, Claudia; Martin, Mike; Horn, Andrea
Abstract: Positivity resonance, the shared experience of emotional positivity, may contribute to the quality of romantic relationships and foster couples' sense of "we-ness". The present study examined age differences in couples' positive experiences in daily life, how they are shared with the partner, and how they are related with "we-ness". In a 21-day experience sampling study, 62 younger (18-33 years) and 54 older (57-87 years) couples reported their momentary positive emotional experiences and disclosure. We-ness was operationalized as the rate of we-pronouns in couples' audio-sensed daily conversations. As hypothesized, daily positivity was associated with we-ness, and older couples experienced more positive affect than younger couples. Older couples also showed higher manifestations of we-ness, and these age differences in we-ness were partially explained by more positive disclosure in daily life. Our results contribute to the literature on socio-emotional positivity and aging by showing how these processes manifest in daily life.